Analysis of risk factors affecting obesity in Korean adolescents: based on the 2017–2020 Korea national health and nutrition examination survey - Kim, Joon Young; Song, Kyungchul; Choi, Youngha; Choi, Byung-Sun; Chae, Hyun Wook (Frontiers in Nutrition, 2025)
BackgroundObesity, which is caused by various congenital factors, lifestyle changes, and modernized eating habits, has recently emerged as a serious health concern in children and adolescents. According to the Korea National Health and Nutrition Examination Survey (KNHANES) conducted from 2007 to 2020, the prevalence of obesity and overweight in youth has shown an increasing trend over time. Notably, obesity has been studied in several studies. However, given its close association with rapidly changing societal environments and lifestyle patterns, continuous updates are necessary. Therefore, investigating the current state of obesity in children and adolescents is crucial. Herein, we investigated factors related to the prevalence of obesity.Materials and methodsWe investigated 1912 adolescents between the ages of 12 and 18 years from 2017 to 2020 using data from the KNHANES. Known and suspected risk factors for lifestyle and eating habits were analyzed using univariate and multivariate logistic regression analyses.ResultsOur study revealed a gradual increase in the proportion of individuals having overweight and obesity. Regarding risk factors for obesity, in the unadjusted model, older age (Odds ratio [OR], 1.11), sedentary time ≥12 h (OR, 1.29), and a higher calorie intake from protein (OR, 1.06) were positively associated with obesity, whereas female sex (OR, 0.52) and sleep duration ≥8 h (OR, 0.56) were negatively associated with obesity. These trends remained consistent in the adjusted model, with older age (OR, 1.10), sedentary time ≥12 h (OR, 1.46), higher protein intake (OR, 1.05), and skipping dinner ≥3 times per week (OR, 2.22) being positively associated with obesity and female sex (OR, 0.60) and sleep duration of 6–8 h (OR, 0.54) and ≥8 h (OR, 0.48) being negatively associated with obesity.ConclusionObesity in Korean adolescents was significantly correlated with shorter sleep duration, more sedentary time, higher protein intake, and frequent meal skipping at dinner. These results highlight the necessity of focused public health initiatives that support healthy living practices, including healthy eating habits, less sedentary activity, and more sleep time.